Utilizing Unified Power Flow Controller for Voltage Stability Improvement of the Electric Power Transmission System of Ghana - William Duodu Asihene; Francis Boafo Effah; Erwin Normanyo (Jurusan Teknik Elektro Universitas Andalas, 2020)
Interconnecting power transmission systems provide reliability of electric power supply. The security of the system is however questioned when a disturbance in any part of the interconnected system causes instability in the entire network. Unified Power Flow Controller (UPFC), which is a member of the flexible alternating current transmission system (FACTS) family, has the capability of controlling active and reactive power flow in a transmission line thereby improving the voltage stability of the system especially at the 500 kV configuration level. The performance of a 161-kV UPFC modelled in SimPowerSystems is tested on Ghana’s power transmission network. The optimal placement of the UPFC is done using fast voltage stability index (FVSI) and maximum loadability assessment (MLA). The results show that the device improved the connecting bus voltage from 0.88 p.u. to 0.98 p.u. Active power loss in the network was also reduced from 13.40 MW to 10.39 MW when the UPFC was in circuit.Keywords: Ghana, Stability, Transmission system and Unified Power Flow Controller (UPFC)